Analysis of Investment Interest in the Capital Market in Management Students of the Faculty of Economics and Business Upn "Veteran" East Java - Siburian, Fredrik Edward; Nur, Dhani Ichsanuddin (Jurnal Ekonomi Balance, 2022)
Interest in investing is a desire to find out about the type of investment starting from the advantages, disadvantages, investment performance and so on. The purpose of this study was to determine the effect of financial literacy, investment knowledge, risk perception on investment interest in the capital market in Management students of the Faculty of Economics and Business UPN "Veteran" East Java. The population in this study were active students of the management study program, the sample was taken using the Slovin formula method which was calculated from the total target population so that a sample of 94 respondents was obtained, the questionnaire method was used for data collection in this study. This study uses Partial Least Square (PLS) as a data analysis technique.The results of this study indicate that financial literacy has a contribution to student investment interest in the capital market, investment knowledge has a contribution to student investment interest in the capital market, risk perception has a contribution to student investment interest in the capital market.